2016
DOI: 10.1371/journal.pgen.1006245
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Mosaic Variants to Autism Spectrum Disorder

Abstract: De novo mutation is highly implicated in autism spectrum disorder (ASD). However, the contribution of post-zygotic mutation to ASD is poorly characterized. We performed both exome sequencing of paired samples and analysis of de novo variants from whole-exome sequencing of 2,388 families. While we find little evidence for tissue-specific mosaic mutation, multi-tissue post-zygotic mutation (i.e. mosaicism) is frequent, with detectable mosaic variation comprising 5.4% of all de novo mutations. We identify three m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
108
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 42 publications
2
108
1
1
Order By: Relevance
“…Several studies detected somatic mutations (postzygotic mutations) in the known risk genes for ASD with the allele fractions ≥ 5% in blood cells from patients with ASD. [55][56][57][58] The relevance of the genes and the large allele fractions indicate early occurrence in development, shared between the brain and the blood. The contribution of such somatic mutations to ASD was estimated to be 3-5%.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies detected somatic mutations (postzygotic mutations) in the known risk genes for ASD with the allele fractions ≥ 5% in blood cells from patients with ASD. [55][56][57][58] The relevance of the genes and the large allele fractions indicate early occurrence in development, shared between the brain and the blood. The contribution of such somatic mutations to ASD was estimated to be 3-5%.…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent reports have demonstrated that PMMs are relatively common in both healthy and neurodevelopmental disorder cohorts, including intellectual disability, ASD, or general developmental delays. 2,26,46,59,60 However, how frequent and widespread these events might be in early and/or late development and how much risk they contribute to complex disorders has yet to be fully elucidated. We found evidence for 11% of SNVs and 26% of indels previously reported as de novo mutations from the SSC Total number of genes differs from full lists as we used only genes that we were able to map to our gene symbol annotations and genes on sex chromosomes were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Freed and Pevsner recently reported on PMM burden in probands and siblings in the SSC. 59 While our two studies used the same SSC datasets, we each used different computational and validation approaches. Restricting our comparison to SNVs at exonic/canonical splice sites, our 453 high-confidence call set contains 470 PMMs in children, 384 that are unique to our study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to de novo germline mutations, a substantial number of de novo somatic mutations (i.e., ~5.4% of de novo events) are detected in the blood of ASD patients and are enriched in ASD probands (22). Somatic mosaic mutations also have been identified throughout postmortem ASD brains or, in some instances, in more localized areas in ASD brains (59).…”
Section: Somatic Mutations In Human Diseasementioning
confidence: 99%